Complex social and environmental interactions within the commodity chain of sericin soap produced by rural sericulture community enterprises in Thailand - Wanasuk, Paphaphit (2019)
Thailand is the first country in the world where the government supports sericulture (silk producing) communities in operating soapmaking businesses based on sericin—a protein isolated from silk wastewater—with the explicit goal of rural economic development. Despite government support (i.e. One Tambon One Product, or OTOP, and Small and Micro Community Enterprise, or SMCE, promotion schemes) and the ongoing expansion of technology transfer to rural communities, little is known regarding the geographies of sericin soap commodity chains, roles and impacts of chain actors, relationships and interdependence between chain actors, and commodity chain impacts. I fill these knowledge gaps and lay a framework for analysis of the environmental impacts of the cosmetics value chain as well as the potential of rural business development to empower female actors. Specifically, this study aims to explicate the complex socioeconomic, cultural, and environmental interactions within the commodity chain of sericin soap produced by rural sericulture community enterprises in Thailand. Adopting a ‘Follow the Thing’ approach, it traces soaps from production in rural Thai communities to market and consumption and analyses the factors that come to light. A collective case study methodology was employed with four case studies to present the realities of the soap commodity system.